Analisis Keterampilan Metakognitif Siswa Sekolah Menengah Atas dalam Pembelajaran Ekonomi Abad 21 di Indonesia - Kodri Kodri; Aan Anisah (FKIP Unswagati, 2020)
AbstractThis study aims to describe the students metacognitive thinking skills in 21st century economic learning in Indonesia. This research is an explanatory survey research with data collection techniques through questionnaire distribution to students. The population in this study were all students of class X and XI of UPI Pilot Laboratory Senior High School as many as 464 people. The sample was taken using the Slovin formula because the total population is less than 1000 people with an error limit of 10% so that a sample of 80 students is obtained. The data of metacognitive thinking skills that have been obtained were analyzed by making a comparable standard measure with the criterion scores of all the indicators summarized in 52 statements that researchers have distributed and distributed to respondents. The results of this study indicate that students metacognitive thinking skills in economic learning as a whole are high, but when viewed from eight indicators that indicators of procedural knowledge and improvement are still relatively low. Therefore, we need a way to develop both indicators.Keywords: Metacognitive Thinking Skills, Senior High School, 21st Century Economic Learning.